2020
DOI: 10.4037/ajcc2020406
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Critical Care Work Environment and Professional Quality of Life

Abstract: Background Professional quality of life is the quality a person feels in relation to work. For critical care nurses, it is composed of compassion satisfaction and compassion fatigue. Professional quality of life is affected by work environment. The American Association of Critical-Care Nurses (AACN) has identified 6 standards for a healthy work environment. Objective To explore which of the AACN healthy work environment stand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
28
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 15 publications
6
28
1
3
Order By: Relevance
“…In the group of physicians, there was no correlation between the variables studied and occupational satisfaction, professional burnout, and compassion fatigue. respect (Jarrad & Hammad, 2020;Monroe et al, 2020). Research conducted among nursing staff indicates large deficits in the implementation of the above conditions, which may be confirmed by the results obtained in the study (Babiarczyk, Fraś, Ulman-Włodarz, & Jarosova, 2014;Kupcewicz, Szczypiński, & Kędzia, 2018).…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…In the group of physicians, there was no correlation between the variables studied and occupational satisfaction, professional burnout, and compassion fatigue. respect (Jarrad & Hammad, 2020;Monroe et al, 2020). Research conducted among nursing staff indicates large deficits in the implementation of the above conditions, which may be confirmed by the results obtained in the study (Babiarczyk, Fraś, Ulman-Włodarz, & Jarosova, 2014;Kupcewicz, Szczypiński, & Kędzia, 2018).…”
Section: Discussionmentioning
confidence: 60%
“…People spend more and more time at work; it has also become more and more complex and demanding. Research shows that the conditions and nature of work, income, employment stability, autonomy and the possibility of professional development are factors that have a significant impact on job satisfaction (Delgado et al, 2020; Monroe, Morse, & Price, 2020; Ruiz‐Fernández, Pérez‐García, & Ortega‐Galán, 2020) To a large extent, this also applies to medical professions where the profession often becomes a social role that imposes a series of duties and obligations on people. Medical professions are characterized by a similar nature: responsibility for the health and life of the patient, working under time pressure, a large number of duties with a shortage of personnel, shift work, etc.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ProQOL measure has been determined to be a reliable and valid instrument through previous research (Dikmen et al, 2016; Fahey & Glasofer, 2016; Monroe, 2020; Stamm, 2005). Internal consistency reliability of the ProQOL measure in this current study was examined using Cronbach's α coefficient.…”
Section: Methodsmentioning
confidence: 99%
“…Other studies have shown that the healthy work environment of Iranian nurses is Inappropriate (Hoseini Es darjani et al, 2018;Salehi et al, 2020). A study by Kim et al (2020) reported a Inappropriate healthy work environment in nurses in Southern California (Kim et al, 2020), while studies in other countries show a appropriate healthy work environment (Huddleston et al, 2017;Kelly and Todd, 2017;Monroe et al, 2020). Studies show that, this difference can be due to the type of management, work culture, authority and different independence of nurses in Iran and abroad.…”
Section: Discussionmentioning
confidence: 99%